PELAKSANAAN PENILAIAN AUTENTIK DI MADRASAH (STUDI PADA GURU MATEMATIKA DI MADRASAH TSANAWIYAN NEGERI 2 BUKITTINGGI) - M. Imamuddin (re-JIEM (Research Journal of Islamic Education Management), 2022)
The 2013 curriculum emphasizes teachers to carry out authentic assessments. Authentic assessment is an assessment that is actually carried out on students. The implementation of this authentic assessment emphasizes the process rather than the results. It is very important for teachers to carry out authentic assessments in the classroom and outside the classroom to students in order to know the progress of student learning. This study aims to analyze the obstacles and solutions of Madrasah mathematics teachers in the implementation of authentic assessments. This research was conducted at Madrasah Tsanawiyah Negeri 2 Bukittinggi. This study involved 4 Madrasah mathematics teachers, hereinafter referred to as research subjects. Data or information related to obstacles and solutions for implementing authentic assessments were obtained through interviews. The results of this study include: Madrasah mathematics teachers encounter obstacles in planning, implementing, and reporting authentic assessments. These obstacles can be solved with solutions: increasing professional competence, participating in various pieces of training, playing an active role in teacher consultation activities both with one madrasa teacher and with outside madrasa teachers, being active in scientific meetings, and further studies such as through teacher professional education and masters degree.